The Implementation of Genre-Based Approach in Teaching Writing at SMA 4 Solok - Widya Syafitri (Politeknik Negeri Padang, 2016)
This research is aimed to describe the way English teachers of SMA 4 Solok implement genre based approach in teachingwriting. This research also investigates the problems found by the English teachers in implementing it and examines how theyovercome those problems. The findings of this research show that the teachers have not implemented genre based approach inteaching writing optimally. Lack of comprehension about the basic principles of genre based approach has been the main cause. Theteachers experienced in familiarizing grammar and vocabulary to the students. It is hard for them to find appropriate materialswhich are close to their life. This study was descriptive qualitative research which was conducted in SMA 4 Solok.